2014
DOI: 10.1590/1678-476620141041513
|View full text |Cite
|
Sign up to set email alerts
|

Variação sazonal no recrutamento de Phragmatopoma caudata (Polychaeta, Sabellariidae) na costa sudeste do Brasil: biometria e validação de metodologia para categorização de classes etárias

Abstract: ABSTRACT. Seasonal variation in recruitment of Phragmatopoma caudata (Polychaeta, Sabellariidae) in the southeast coast of Brazil: validation of a methodology for categorizing age classes. This study explores the achievement of gametes maturity and biometric analysis of Phragmatopoma caudata Krøyer in Mörch, 1863 to endorse a methodology and provide a proper technique for studies aiming to assess the population ecology. Analysis via Pearson's test confirmed a significant evidence of positive correlation (r = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Gregarious sabellariids, such as members of Gunnarea , Paraidanthyrsus, Sabellaria , Phragmatopoma, and Neosabellaria, are known to build large clumps or even large reefs in intertidal habitats, and therefore larvae seem to be able to detect conspecific individuals (Kirtley ; Bailey‐Brock et al. ; Faroni‐Perez ; Firth et al. ; Nishi et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gregarious sabellariids, such as members of Gunnarea , Paraidanthyrsus, Sabellaria , Phragmatopoma, and Neosabellaria, are known to build large clumps or even large reefs in intertidal habitats, and therefore larvae seem to be able to detect conspecific individuals (Kirtley ; Bailey‐Brock et al. ; Faroni‐Perez ; Firth et al. ; Nishi et al.…”
Section: Discussionmentioning
confidence: 99%
“…; Desroy et al. ; Faroni‐Perez ; Firth et al ), but in other species individuals live in small clumps or are found as solitary individuals (Hutchings et al. ).…”
mentioning
confidence: 99%
“…Phragmatopoma caudata likely has large population sizes, as the density of individuals has been estimated at c . 65,000 individuals m − ² (Faroni‐Perez, ). Given that the generation time of P. caudata is of 1 year, a large fraction of individuals potentially contribute to the gene pool each year.…”
Section: Discussionmentioning
confidence: 99%
“…Phragmatopoma caudata (as P. lapidosa Kinberg, 1866) reproduces by external fertilization of gametes that are produced year‐round (Eckelbarger, ). Spawning and recruitment are highest in the summer months, from June to August in Florida, USA (McCarthy et al ., ), and February to April in São Paulo State, Brazil (Faroni‐Perez, ). Fecundity is high, as the average female can spawn 1500–2000 oocytes (McCarthy et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some species are gregarious and their cemented tubes form reef-like structures of hundreds to millions of individuals that can extend over several kilometres along the coast (e.g., Achari 1974;Kirtley 1974;Caline et al 1988Caline et al , 1992McCarthy et al 2008;Barrios et al 2009;Faroni-Perez 2014).…”
Section: Introductionmentioning
confidence: 99%